Anne Frank : the Anne Frank House authorized graphic biography - Jacobson, Sidney (Hill and Wang, 2010)
Provides a graphic novel account of the life of Anne Frank, covering her family, the rise of Nazism, her years in the Secret Annex, her arrest, her deportation, her death, her father's recovery of her diary, and other related topics.